Confirmatory Search and Asymmetric Dominance1. (9th June 2014) - Bhatia, Sudeep
ABSTRACT Decision makers use confirmatory search strategies in judgment tasks. As a result of this, their attention towards task‐relevant cues is biased in favor of cues supporting available responses. Changing these responses can alter the cues used in the judgment task and, subsequently, alter beliefs. We use this mechanism to predict and explain the emergence of the asymmetric dominance effect in judgment. In four sets of experiments, we document systematic changes in belief, as dominated options are added to the response set. These effects emerge for a number of naturalistic judgment tasks and are mediated by the increased accessibility of decoy‐supporting cues. Finally, these effects can be eliminated when the decision maker's attention is drawn towards the cues supporting the non‐dominant response. Copyright © 2014 John Wiley & Sons, Ltd.